Cerebral Palsy A Practical Guide for Rehabilitation Professionals - Giannoni, Psiche; Zerbino, Liliana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book helps rehabilitators and caregivers understand the multifaceted needs of children with cerebral palsy or other neuromotor impairments in order to plan and implement an effective treatment regimen. Drawing on the authors$1 (Bextensive experience spanning several decades, it addresses the sensitive challenge of rehabilitation, which cannot and must not be confined by the rigid schemes of established schools. In particular, the book provides numerous practical suggestions, intended to guide the reader through correct clinical reasoning, setting goals and subsequent treatment. Furthermore, it includes chapters on evaluating and treating the upper limbs, feeding and communication problems, as well as on the care of soft tissues and the management of the visual difficulties in these children. The book is a valuable resource for physiotherapists, occupational therapists, speech therapists and other caregivers.s
Chapter 1) Child Evaluation Guide and Clinical Reasoning -- Chapter 2) The Child with Bilateral Spastic Cerebral Palsy -- Chapter 3) The Child with Unilateral Spastic Cerebral Palsy -- Chapter 4) The Child with Dyskinesia -- Chapter 5) Ataxia in Cerebral Palsy -- Chapter 6) Sensory-Motor and Perceptual Problems in Cerebral Palsy -- Chapter 7) Therapeutic Approaches for the Soft Tissues -- Chapter 8) Guidelines for Upper Limb Rehabilitation -- Chapter 9) Upper Limbs Functional Problems in Different Forms of Cerebral Palsy -- Chapter 10) Feeding and Dysphagia in Children with Cerebral Palsy -- Chapter 11) The Child with Cerebral Palsy and Visual Impairment -- Chapter 12) Augmentative and Alternative Communication in Severe Motor Impairment -- Chapter 13) Rehabilitation Technologies for Sensory-Motor-Cognitive Impairments.
Keywords: Physical therapy; Physiotherapy; Cerebral Palsy -- rehabilitation; Infant; Child